Mindful Social Work? - Raf Debaene (Social Work and Society)
Mindfulness gets growing attention in the education and practice of social work. It is seen as an important source of inspiration for social work and as a counterbalance for the rationalization of social work. Hick states that mindfulness"is an orientation to our everyday experiences that can be cultivated by means of various exercises and practices. By opening up in a particular way to their internal and external experiences, social workers and clients are better able to understand what is happening to them in both a psychological and sociological sense. With this understanding, people are better able to see the variety of ways in which they can respond. Habitual reactions are more easily avoided, and inner peace and balance are developed" (Hick 2009: 1). Despite this praise of mindfulness as an important source of inspiration and the expectation that its popularity might expand in the next century, it is argued in this essay by Raf Debaene that mindfulness, although possibly very useful in some settings, had very little to do with social work.